ORGANIZATION, COMPONENTS AND SYSTEM OF VERBAL COMMUNICATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines issues related to the organization, composition, and system of verbal information exchange process (speech communication), which includes the transmission and reception of messages that form the cycle of dialogic speech. The components of this process are: addresser, expressed information, and addressee, while the system of verbal communication includes the following components: environment, style, theme, direction, object, place, time, condition, situation, mood, attitude, interest, individual characteristics of participants, as well as logic, psychological situation, importance, necessity, and other equally important factors that have a direct impact on the effectiveness of verbal communication.
Keywords: verbal information exchange processes, organization of verbal communication, components and systems of verbal communication, text, addresser, expressed information, addressee, verbal communication policy, etc